PENYULUHAN TENTANG ANEMIA PADA REMAJA SMAN 14 BANDAR LAMPUNG KEMILING PERMAI TANJUNG KARANG BARAT LAMPUNG TAHUN 2020 - Sunarsih M.Kes; Melani Komara Sari; Reza Fadhillah; Riski Novita Ratna; Sartiah Sartiah (Program Studi Kebidanan Fakultas Kedokteran, 2020)
According to World Health Organization (WHO), the anemia's prevalence toward teenager in the world is 4,8 million and the amount of indonesia is a 23%. Based on the result of a basic health research, anemia's number in Indonea is still high. Various reasons that stated by teenager about why they do not consume balanced nutrition ,because they are strict diet and do not understand yet about bad impact of anemia . The aim of this activity is hoped that citizen can understand about anemía for teenager and the impact of it. This activity was done on thursday, 06 february 2020. Then, form of the activity Is in the forming of counseling to teenager about anemia and the way to overcome it at Senior High School 14 Bandar Lampung by counseling method, using power point . There was a significant Influence on teenager knowledge before and after anemia counseling for teenager . Thus, the provision of education can provide increased knowledge , particularly those related to anemia when teenagre.